CHRONIC MYELOPROLIFERATIVE NEOPLASMS: A COMPREHENSIVE REVIEW - Jakhonov Azizbek Kholmirzaevich,; Matkarimova Dilfuza Saburovna, (TADQIQOTLAR, 2025)
Abstract Chronic myeloproliferative neoplasms (MPNs) are clonal hematopoietic stem cell disorders characterized by the overproduction of one or more types of blood cells. These disorders are typically slow-progressing but may evolve into acute leukemia or bone marrow failure over time. This review provides an in-depth discussion of the main types of Ph-negative MPNs: polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF). It covers their clinical features, genetic mutations, diagnostic criteria, treatment approaches, and prognosis.